2013
DOI: 10.1038/nature12522
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a new nuclear ‘magic number’ from the level structure of 54Ca

Abstract: Atomic nuclei are finite quantum systems composed of two distinct types of fermion--protons and neutrons. In a manner similar to that of electrons orbiting in an atom, protons and neutrons in a nucleus form shell structures. In the case of stable, naturally occurring nuclei, large energy gaps exist between shells that fill completely when the proton or neutron number is equal to 2, 8, 20, 28, 50, 82 or 126 (ref. 1). Away from stability, however, these so-called 'magic numbers' are known to evolve in systems wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
349
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 380 publications
(400 citation statements)
references
References 29 publications
38
349
1
2
Order By: Relevance
“…Although the absolute energy scale depends on the overall mass region, and may be influenced by other structural properties (e.g., effects of triaxiality or single magicity), the evolution of the E(2 + 1 ) over a series of isotopes is often the first indicator for the evolution of structures, and can test or guide nuclear theory. A recent example is the location of a new doubly-magic Ca isotope at N = 34 through measurement of its E(2 + 1 ) values [7] by γ-spectroscopy after proton-knockout at the RIKEN Radioactive Ion Beam Factory (RIBF).…”
Section: Introductionmentioning
confidence: 99%
“…Although the absolute energy scale depends on the overall mass region, and may be influenced by other structural properties (e.g., effects of triaxiality or single magicity), the evolution of the E(2 + 1 ) over a series of isotopes is often the first indicator for the evolution of structures, and can test or guide nuclear theory. A recent example is the location of a new doubly-magic Ca isotope at N = 34 through measurement of its E(2 + 1 ) values [7] by γ-spectroscopy after proton-knockout at the RIKEN Radioactive Ion Beam Factory (RIBF).…”
Section: Introductionmentioning
confidence: 99%
“…Shell structure influences the locations of the neutron and proton drip lines and the stability of matter. Examples of changes in shell structure are the appearance of new magic numbers N = 14 and N = 16 in the neutron-rich oxygen isotopes [1,2], and the emergence of an N = 34 sub-shell closure in 54 Ca [3][4][5][6].Phenomenological shell-model Hamiltonians such as the sd Hamiltonian of Brown and Wildenthal [7,8] (abbreviated USD) and the p-sd Hamiltonian of Warturburton and Brown [9] (abbreviated WBP), have successfully described properties of nuclei with proton number Z and neutron number N less than about 20. To understand the origin of shell structure, however, researchers are now trying to derive the shell model from realistic nucleonnucleon (NN) and three-nucleon forces (3NFs), without further phenomenology [3,10,11].…”
mentioning
confidence: 99%
“…Shell structure influences the locations of the neutron and proton drip lines and the stability of matter. Examples of changes in shell structure are the appearance of new magic numbers N = 14 and N = 16 in the neutron-rich oxygen isotopes [1,2], and the emergence of an N = 34 sub-shell closure in 54 Ca [3][4][5][6].…”
mentioning
confidence: 99%
“…The magic numbers for stable nuclei were first successfully described by invoking a one-body square-well and spin-orbit potential [4,5]; the latter was eventually replaced by a harmonic oscillator potential with l 2 term to obtain proper angular momentum splittings [6]. However, studies of radioactive nuclei over the past decades have shown that the magic numbers are not universal across the nuclear chart [7][8][9][10]. Despite intensive e↵ort, the theoretical description of these structural changes is not yet fully understood and the mechanisms that drive structural evolution di↵er between models.…”
mentioning
confidence: 99%